Prevalence and clinical correlates of antiphospholipid antibodies in South Africans with systemic lupus erythematosus - Gould, Trevor John (My University, 2008)
ABSTRACT OBJECTIVE: To determine the prevalence and clinical correlates of anti-phospholipid antibodies (aPL), including anti-cardiolipin antibodies (aCL), lupus anti-coagulant (LA), anti- β2-glycoprotein 1 (aβ2GP1) and anti-prothrombin (aPT) antibodies, in Black South African patients with systemic lupus erythematosus (SLE) METHODS: A cross-sectional study of 100 SLE patients in whom clinical characteristics, including features of the anti-phospholipid syndrome (APS), disease activity, and damage were documented, and sera tested for aCL, aβ2GP, and aPT of all isotypes, and LA. RESULTS: Positive aCL, aβ2GP1 and aPT and LA were found in 53, 84, 20, and 2 patients, respectively. Immunoglobulin (Ig)A aCL and IgG aβ2GP1 were the commonest aCL (49.1%) and aβ2GP1 (47%) isotypes, respectively. IgA aβ2GP1 were associated with both a history of thrombosis alone (p<0.05) and a history of any clinical feature, thrombosis and/or spontaneous abortion of the APS (p<0.05); IgA aCL were associated with a history of any clinical APS event (p<0.05); and aβ2GPI of any isotype were associated with a history of arthritis (p<0.001). CONCLUSION: My findings provide further evidence that the screening for aβ2GP1 and IgA aCL isotype may improve the risk assessment for APS in SLE patients of African extraction. Further prospective studies are warranted to determine the clinical utility of these tests and to elucidate the genetic basis for increased IgA aPL response in SLE patients of African extraction.
Keywords: antiphospholipid antibodies; systemic lupus erythematosus; SLE